THE SYADZILIYAH SUFI ORDER AT PETA ISLAMIC BOARDING SCHOOL, TULUNGAGUNG: SPIRITUAL TRADITIONS AND MORAL DEVELOPMENT - Harisatun Naila Rofiah (Satmata: Journal of Historical Education Studies, 2025)
This study aims to examine the role of the Syadziliyah Sufi Order at Pondok Peta Tulungagung as a spiritual tradition that contributes to the reinforcement of morality and character within the community. The order emphasizes Sufi practices such as dhikr, bai'at, and haul to foster spiritual closeness to God and to cultivate individual morality. Employing a descriptive qualitative approach, data were collected through participatory observation, in-depth interviews, and document analysis. The findings indicate that the teachings of the Syadziliyah Order, under the guidance of a mursyid (spiritual guide), have a positive impact on spiritual well-being, character education of the students (santri), and social solidarity. Furthermore, the integration of Sufi values into daily life proves to be relevant in addressing the challenges of modernity in both spiritual and social contexts. The Syadziliyah Order not only strengthens individual moral and ethical values but also fosters a harmonious and compassionate community.